The Effectiveness of Role-Play on Primary Students’ English-Speaking Skills in Indonesian EFL Classroom: Qualitative Meta-Analysis - Nailus Sa'adah; Nuskhan Abid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
English speaking skills remain a challenge for elementary school students in Indonesia in the context of English as a Foreign Language (EFL). Limited vocabulary, low self-confidence, anxiety when speaking, and limited opportunities for communication practice hinder students' speaking skills. The role-play method is considered adequate for overcoming these problems because it provides students with opportunities to use English in meaningful, real-life situations. This study aims to synthesise empirical findings on the effectiveness of the role-play method in improving the English-speaking skills of elementary school students in Indonesia. This study uses a qualitative meta-analysis approach, following the PRISMA 2020 guidelines. Data were obtained from journal articles published between 2015 and 2025 through the Google Scholar database. Of the 17,600 articles identified, 10 that met the inclusion and exclusion criteria were analysed using thematic analysis. However, this study has limitations because it relies solely on Google Scholar, potentially excluding other relevant studies from the analysis. The results showed that the role-play method was effective in improving students' speaking skills across linguistic, affective, and social interaction aspects. Improvements included vocabulary mastery, fluency, confidence, learning motivation, and student activity. In addition, role play encourages meaningful interaction and creates a learning environment that supports English-speaking practice. To maximise results, role-play needs to be applied through scenarios relevant to students' context, explicit teaching of vocabulary and expressions, guided role-play practice, and systematic teacher feedback. Thus, role play is an effective and targeted method for improving the speaking skills of elementary school students.